The pragmatic language, communication skills, parent–child relationships, and symptoms of children with ADHD and their playmates 18-months after a parent-delivered play-based intervention - Wilkes-Gillan, S.; Cantrill, A.; Parsons, L.; Smith, C.; Cordier, Reinie (Informa Healthcare, 2016)
Objective: This study examined the communication skills, pragmatic language, parent–child relationships, and attention deficit hyperactivity disorder (ADHD) symptoms of children with ADHD and their playmates 18-months after a pilot parent-delivered intervention for improving social play skills and pragmatic language. Methods: Participants were five children with ADHD, their parents, and five typically-developing playmates. Outcomes were measured immediately post and 18-months following the intervention. Parent-rated norm-based assessments and an observational measure were used. Differences within and between the ADHD and playmate groups were examined. Results: Children maintained all skills gained 18-months following the intervention. Compared to a normative sample, children with ADHD remained below the average range on aspects of communication skills, parent–child relationships, and ADHD symptom levels 18-months following intervention. Conclusions: After intervention, children with ADHD still experienced pragmatic language skills below those of their peers on norm-based assessments that measure their skills across contexts. School-based interventions are needed to facilitate ongoing skill development and generalization.